Certain Fractional Integral Formulas Involving the Product of Generalized Bessel Functions. (28th November 2013) - Baleanu, D.; Agarwal, P.; Purohit, S. D.
Abstract : We apply generalized operators of fractional integration involving Appell's function F 3 ( · ) due to Marichev-Saigo-Maeda, to the product of the generalized Bessel function of the first kind due to Baricz. The results are expressed in terms of the multivariable generalized Lauricella functions. Corresponding assertions in terms of Saigo, Erdélyi-Kober, Riemann-Liouville, and Weyl type of fractional integrals are also presented. Some interesting special cases of our two main results are presented. We also point out that the results presented here, being of general character, are easily reducible to yield many diverse new and known integral formulas involving simpler functions.